Desorption Electrospray Ionization Mass Spectrometry Imaging Illustrates the Quality Characters of Isatidis Radix - Nie, Li-Xing; Huang, Lie-Yan; Wang, Xin-Ping; Lv, Lin-Feng; Yang, Xue-Xin; Jia, Xiao-Fei; Kang, Shuai; Yao, Ling-Wen; Dai, Zhong; Ma, Shuang-Cheng (Frontiers in Plant Science, 2022)
For a long history, herbal medicines have made significant contribution to human health all around the world. But the lack of rigorous quality control had hindered their development in modern times. So it is imperative to develop new methods and technologies to characterize and identify quality markers of herbal medicines. Taking Isatidis Radix, the dried root of Isatis tinctoria L. (Brassicaceae) as an example, desorption electrospray ionization (DESI), in combination with quadrupole-time-of-flight mass spectrometry (Q-TOF/MS), was applied in this work for the first time to reveal comprehensive spatial distribution of metabolites, and further, to illustrate quality characters of this herbal medicine. After simple pretreatment, 102 metabolites including alkaloids, sulfur-containing compounds, phenylpropanoids, nucleosides, amino acids, organic acids, flavonoids, phenols, terpenes, saccharides, peptides and sphingolipids were characterized, some of which were successfully localized and visualized in the transverse section of the root. Based on the ion images, samples with different quality characters were distinguished unambiguously by the pattern recognition method of orthogonal partial least squares discrimination analysis (OPLS-DA). Simultaneously, 10 major influencing components exerting higher ion intensities in superior samples were identified as the potential quality markers of Isatidis Radix. Desorption electrospray ionization (DESI) mass spectrometry imaging (MSI), together with chemometric analysis could not only improve the understanding of the plant biology of herbal medicines, but also ensure the effectiveness of their medicinal use.